Connection Between Civil Service and Personal Development - Zsuzsa Darida (DETUROPE)
The public administration of the modern age and the significant changes taking place in the public administration in these days gave rise to the lecture. After a brief review of the historical antecedents a multi-stage process of reforms is mentioned as a result of which the so called closed system of public administration of Hungary became loose in a sense and the stiff margins which hindered the realization of the human resource management functions and presented a parting line between the establishments of the civil service and the competitive sector have been altered in a certain way. The present study deals with the direction towards which the present system proceeds and also with some management functions (e.g. performance evaluation) the importance of which is stressed greatly in the past few years. Finally a new field of research is dealt with which examines the efficiency of the personal development trainings as a special segment of these changes.